Educação ambiental na escola do campo : processos, procedimentos e práxis pedagógicas no contexto escolar - Sanches, Denise Godoi Ribeiro (2016)
Environmental education emerges from the reflection of the discussions on the global environmental crisis, aroused in international and national meetings with strategies for basic education, higher and graduate, as well as to the levels of government, social movements and civil society in order to contribute for the formation of critical, reflective and participatory citizen, able to make decisions in the various spheres of society. This paper presents the partial results of the research on environmental education in a school of public state of Paraná, in the "Field" mode, with the overall objective to recognize the practice of environmental education in the school field, in accordance with the procedures , procedures and pedagogical practices developed by teachers, teaching staff and educational agents I and II and the theoretical framework of environmental education and field. The methodological field is of a qualitative nature of the theoretical references of action research. For procedures of methodological analysis (semi-structured interviews and documentary research) to unveil the survey data, referenced in the content and document analysis of the Curricular Guidelines of the State of Paraná Basic Education, Political Pedagogical College Project and Plans work of the research members of the Faculty. Partial considerations listed are that environmental education is not included in all curriculum guidelines of the state of Paraná basic education (DCEs). The Pedagogical Political Project of the college there is an emphasis on environmental education and it is disjointed and outdated before the PPP base reference (DCNs, DCEs, Laws of EA and Rural Education). As for the plans of teachers studies analyzed, the Environmental Education assumptions and field of education were found in a few PTD and not have to focus only with ideas that could be worked by some teachers. Compared to the interviews we believe that these teachers aware of the importance of developing environmental education activities in education but have no training in environmental education and field sufficient to contribute to the formation of citizens able to make environmental decisions with a positive impact on society even so, some interviewed teachers develop activities related to environmental education, with examples in agricultural activities, according to their capabilities and knowledge of the subject in their specific areas of expertise.